PENGARUH CSR TERHADAP NILAI PERUSAHAAN DENGAN MODERASI PROFITABILITAS - Fellycia Fellycia; Lodovicus Lasdi (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2021)
Complex company activities often cause environmental damage. One form of corporate responsibility efforts in suppressing or preventing such damage is to carry out Corporate Social Responsibility (CSR). CSR disclosure has become a must for every company that can provide tangible evidence of the company's participation in people's lives. This study was conducted to determine how the influence of CSR by using profitability as a moderator on firm value. Manufacturing companies that have been listed on the IDX with a period spanning 2016-2019 are taken as research objects. A total of 65 samples have been selected through purposive sampling method. Analysis related to the established hypothesis was carried out using multiple linear regression. This study resulted in a conclusion that there was a positive and significant effect of CSR on firm value, however, the use of profitability as a moderation could not give the effect of CSR to increase firm value.